Green synthesis of nanomaterials: An overview. (2021) - Aarthye, P.; Sureshkumar, M.
Abstract: Nanotechnology has grabbed the attention of Chemists, Physicists, Biologists and Engineers by synthesizing nanoparticles with escalated properties than bulk materials. These nanoparticles find varied applications with certain modifications in their surface morphology. Physical and chemical route of synthesis of nanomaterials over a number of years in the recent past have authenticated harmful toxic effects on humans. This scenario powered the researchers to lean towards green synthesis of nanoparticles. This new method of synthesis shows decrease in toxic effects of nanoparticles over the environment and humans by integrating the available metabolites in biological extracts making them biocompatible. This review analyses the various methods of utilizing biological extracts for the synthesis nanoparticles and their advantages.